Desain dan Analisis Pembebanan Statis Klem Penahan Pipa Air - Jhon A. Wabang; Paula Rita; Jonri L. Ga; Hero P. Dida; amros tuati (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
This This study aims to design and analyze static loading on a metal water pipe clamp using Finite Element Analysis (FEA) based simulation in Solidworks. The analysis was performed at four static loading variations: 250 N, 500 N, 750 N, and 1000 N, to determine the structural response in terms of stress, displacement, strain, and safety factor. The simulation results show that increasing the loading force significantly affects the stress and deformation values. At 250 N, the clamp remains secure with a high safety factor. Then, at 1000 N, the stress and strain increase significantly, and the safety factor decreases, approaching the material's safety limit. Overall, the clamp design is still capable of supporting loads up to 1000 N. However, shape optimization or increasing the material thickness is needed to improve safety when used under continuous heavy load conditions. The highest von Mises stress is 8.512e-07 N/mm2, displacement 9.041e+2 mm, strain 2.140e-04 N/mm2 and safety factor 2.609e+01.